Facile synthesis of 2-substituted benzo[b]furans and indoles by copper-catalyzed intramolecular cyclization of 2-alkynyl phenols and tosylanilines. Issue 31 (7th June 2019) - Rong, Zhouting; Gao, Kexin; Zhou, Lei; Lin, Jianyuan; Qian, Guoying
Abstract : A facile and inexpensive copper-catalyzed method was developed for the synthesis of 2-substituted benzo[ b ]furans and indoles. Abstract : A catalytic amount of CuCl and Cs2 CO3 was employed to synthesize a variety of 2-substituted benzo[ b ]furans and indoles by an intramolecular cyclization of 2-alkynyl phenols and tosylanilines. This protocol features mild conditions, high yields and broad substrate scope, which makes it a practical method for the synthesis of 2-substituted benzo[ b ]furans and indoles.